ANALISIS KESADARAN HALAL PADA PELAKU USAHA MIKRO KECIL DI SEKITAR KAMPUS UNIVERSITAS TRUNOJOYO MADURA - Zaman, Badrus; Faraby, Muhammad Ersya (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2023)
In today's developments, the most common object for business actors is small businesses such as selling food, snacks and others. People need to ensure that the products they consume are halal and their halalness is guaranteed by the government. This research aims to see the results of halal awareness among business actors. micro and small businesses around the Trunojoyo Madura University campus, this research uses qualitative methods because it collects information through interviews, observation, documentation and analysis of informant data with 10 micro and small business actors around the Trunojoyo Madura University campus, thereby producing data analysis and getting appropriate answers with informants, this research data also uses primary and secondary data techniques. The results of the research show the level of halal awareness of micro and small business actors around campus, one of which said that it depends on the flow that a person follows and some of them remain by Islamic law.